Performance study of automatic transmit power control (ATPC) in point to point microwave link for rain attenuation problem in Malaysia - Saad, Muhamad Mokhtar (2006)
Point-to-point microwave system is the backbone link for mobile communication industry as well as for other applications. In tropical region particularly in Malaysia, rain attenuation is the major constraint for implementing microwave system above 10GHz. The extreme of propagation channel environment due to rain has brought to the research and development of an automatic transmit power control (ATPC) in microwave transceiver. ATPC varies the transmit power level in order to maintain the receive signal level (RSL) above the threshold for biterror- rate (BER) desired. This research project will cover three main scope of study. First estimated calculation of rain attenuation on terrestrial point-to-point microwave link based on rain data captured. This will involve the understanding and computational of rain attenuation modeling equation by ITU-R recommendation using the Matlab software. Second is the basic concept and operational of ATPC applied in transceiver module of microwave link. Finally the experimental performance analysis of ATPC on actual microwave link install in Celcom microwave network. The performance will be measured on receive signal level on the actual system with ATPC option enable and disable for a certain period of time with realtime rain faded signal